Ancient Beliefs in the Primordial Forces of Sacred Waters and their Religious Implications in an Aladura Church in Nigeria - Alabi, David O.; Tunase, Christian T.; Olowookere, Felicia A.; Olufemi, Olukunle J.; Tukasi, Emmanuel O. (NIU Journal of Humanities, 2024)
Water has a central place in ancient myths of creation and mythologies and it has never been viewed as an ordinary element but as having both spiritual and physical potentials and properties in religious circles as well as an elemental force in nature. It has symbolically represented many things in religions, humanity and waters were given mythological venerations in many stories of the ancient Mesopotamian world.  The gap filled in this study was the nexus of primordial waters and its implications in the liturgy of a foremost Aladura church, Christ Apostolic Church, which has not been given scholarly considerations and presented. The goal of the paper is to espouse the ancient beliefs in the primordial forces of waters and their cosmic significance to the humans and their implications in the liturgy of the this Aladura church. As a result, this paper is premised on the relevance of water to religions as the ancient people viewed it and its roles in the liturgy of CAC. It used the historical-traditional methods of approach to unravel the mysteries believed to be associated with waters in religions. The study espoused the marriage of water and creation, living entity and procreation force in water and as a cogent healing instrument in the liturgy of the church. The forces and properties of water and its significance in religions are brought into focus in this piece, the crux of this paper is the religious significance of water in this Aladura Church, Christ Apostolic Church, Nigeria and Overseas in her healing ministrations. Findings showed that water is a living entity in many religions and prominently featured in the liturgy of this Aladura denomination thereby buttering contextualization of Christian religion in African context. Keywords: Primordial Waters, Forces, Implications, Liturgy, Aladura Church